2006
DOI: 10.1007/s00425-006-0261-9
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive expression profiling of the pectin methylesterase gene family during silique development in Arabidopsis thaliana

Abstract: Pectin methylesterases (PME, EC. 3.1.1.11) are enzymes that demethylesterify plant cell wall pectins in muro. In Arabidopsis thaliana, putative PME proteins are thought to be encoded by a 66-member gene family. This study used real-time RT-PCR to gain an overview of the expression of the entire family at eight silique developmental stages, in flower buds and in vegetative tissue in the Arabidopsis. Only 15% of the PMEs were not expressed at any of the developmental stages studied. Among expressed PMEs, express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(124 citation statements)
references
References 49 publications
(67 reference statements)
7
117
0
Order By: Relevance
“…PMEs interacting with AtPMEI-1 and AtPMEI-2 were identified as AtPME3 (At3g14310), shown to be mainly expressed in Arabidopsis hypocotyls, leaves, and roots (Micheli et al, 1998;Pina et al, 2005;Louvet et al, 2006) and At2g43050 mainly expressed in siliques and stems (Micheli et al, 1998;Pina et al, 2005;Louvet et al, 2006; see also the gene expression database: http://csbdb.mpimp-golm.mpg.de/). The finding that both PMEs were associated with both inhibitors is consistent with the large spectrum of recognition played by the inhibitors (Mattei et al, 2002;Ciardiello et al, 2004;Raiola et al, 2004;Di Matteo et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…PMEs interacting with AtPMEI-1 and AtPMEI-2 were identified as AtPME3 (At3g14310), shown to be mainly expressed in Arabidopsis hypocotyls, leaves, and roots (Micheli et al, 1998;Pina et al, 2005;Louvet et al, 2006) and At2g43050 mainly expressed in siliques and stems (Micheli et al, 1998;Pina et al, 2005;Louvet et al, 2006; see also the gene expression database: http://csbdb.mpimp-golm.mpg.de/). The finding that both PMEs were associated with both inhibitors is consistent with the large spectrum of recognition played by the inhibitors (Mattei et al, 2002;Ciardiello et al, 2004;Raiola et al, 2004;Di Matteo et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…PttPME1 Is an Abundant PME Involved in Xylogenesis PME is a ubiquitous enzyme in plants, encoded by 66 genes in Arabidopsis (Arabidopsis thaliana), most showing tissue-and stress-specific expression patterns (Louvet et al, 2006;Pelloux et al, 2007; http://www. afmb.cnrs-mrs.fr/CAZY/CE_8.html).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, PMEI-related proteins are encoded by a large multigene family with 69 members, with only PMEI6 associated with a loss-offunction phenotype. Future studies will be required to identify the PME protein target(s) of PMEI6 and SBT1.7; in silico data and promoter:GUS constructs have shown that several of the 66 members of the PME gene family are expressed in seed tissues and seven PMEs appear to be strongly expressed in the seed coat (Louvet et al, 2006;Le et al, 2010). It will also be important to determine the precise nature of their HG substrates and to elucidate how PME activity is fine-tuned in seed coat epidermal cells.…”
Section: Transcriptional Regulation Of Hg Methylesterification In Seementioning
confidence: 99%